POWER RELATIONS AND PUBLIC CONTESTATION: AN ANALYSIS OF GOVERNOR DEDI MULYADI'S "MILITARY BARACKS" POLICY - Ely Yani; Noor Rachmat, Farahdiba; Sitorus, Ruth Edri Paulina; Pratiwi, Shinta Indri (Jurnal Sosiologi Dialektika Sosial, 2025)
This study aims to analyses the "military barracks" policy initiated by the Governor of West Java, Dedi Mulyadi as a response to juvenile delinquency as well as a complex product of power. The analytical framework uses the three-dimensional theory of power by Lukes and the sources of power by Mann to explain the political, military, and ideological interactions in public policy formation. The research method is a single case study with a Qualitative Content Analysis (QCA) approach. The data comes from the 12 most accessed national news and is strengthened by secondary data from the Indonesian Political Indicators survey (2025) regarding the level of public acceptance of this policy. The analysis is carried out through pre-processing of the text, identification of actors and concepts, the construction of discourse networks, and the calculation of network metrics to map the centre of power and framing of discourse. The results of the study show that the military barracks policy is an arena for the articulation of social forces that interact with each other. The program emphasizes how formal and symbolic power synergize to build legitimacy, while still provoking public debate about children's rights and the effectiveness of militaristic approaches. This study also found that the military barracks policy is a concrete example of how power is interpreted, exercised, and debated. This policy represents the dynamics of democracy at the regional level. Policy is not only a product of the executive branch, but an interaction between political, military, media, public and legislative actors who mutually test the limits of power.